2021
DOI: 10.1002/dc.24760
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Oil‐Red‐O positive macrophages in bronchoalveolar lavage in diagnosing E‐cigarettes or vaping product use‐associated lung injury: A case series

Abstract: BackgroundLipid‐laden macrophages detected by Oil‐Red‐O (ORO) stain in fresh bronchoalveolar lavage (BAL) specimens have been proposed as a potential diagnostic marker for E‐cigarettes or vaping product use‐associated lung injury (EVALI). However, studies are few, and the sensitivity and specificity of the test have not been thoroughly investigated.MethodsWe performed ORO stain on fresh BAL specimens from six confirmed EVALI and 36 non‐EVALI patients. After semi‐quantitative analysis, the sensitivity and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thus, impairment in the function of these key macrophages might result in tumor promotion and worsened clinical outcomes. Moreover, studies have also found that there is an increased presence of lipid-laden macrophages correlated to e-cigarette or vaping product use-associated lung injury [55]. Lipid-laden alveolar macrophages are often indicators of aspiration and may serve as markers for lung disease [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, impairment in the function of these key macrophages might result in tumor promotion and worsened clinical outcomes. Moreover, studies have also found that there is an increased presence of lipid-laden macrophages correlated to e-cigarette or vaping product use-associated lung injury [55]. Lipid-laden alveolar macrophages are often indicators of aspiration and may serve as markers for lung disease [56,57].…”
Section: Discussionmentioning
confidence: 99%